Thermal resistance measurement of In3SbTe2 nanowires. Issue 5 (19th December 2016) - Battaglia, J.‐L.; Saci, A.; De, I.; Cecchini, R.; Selmo, S.; Fanciulli, M.; Cecchi, S.; Longo, M.
Abstract : The thermal resistance along the thickness of In3 SbTe2 crystalline nanowires was measured using the scanning thermal microscopy in 3 ω mode. The nanowires were grown by metal organic vapor deposition, exploiting the VLS mechanism induced by Au metal‐catalyst nanoparticles and harvested on a SiO2 /Si substrate. Two nanowires with different thickness (13 and 23 nm) were investigated. The thermal resistance of the nanowires was determined using two different approaches; the first one exploits the experimental data, whereas the second one is more sophisticated, since it involves a minimization procedure. Both methods led to comparable values of the thermal resistance along the transverse direction (thickness) of the nanowire. The obtained results were explained starting from the mean free path of phonons calculated in the In3 SbTe2 bulk.